Used of Turmeric in Handling Myiasis in Bali Cattle in North Sinjai District, South Sulawesi - Rell, Fedri; Jamilah, Ainun; Ris, Adryani; Purba, Fika Yuliza; Jamaluddin, Abdul Wahid; Apada, Andi Magfira Satya; Yusuf, Baso; Suharto, Rian Hari; Kholilullah, Zainal Abidin; Rasdiyanah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2025)
Myasis is a disease that commonly occurs in ruminants with the incidence of myasis increasing from year to year in Indonesia, especially in rural areas, with an incidence rate of 70% and a recurrence rate of up to 40% in cattle, buffalo, horses and goats. This disease is characterized by the presence of wounds and maggots. The presence of secondary infections will make the disease worse. Therefore, it is necessary to handle miasis cases so that they do not cause losses to farmers. A 7 year old of bali cattle in the North Sinjai district experienced miasis on the head. Treatment for myasis includes washing the wound, removing maggots and administering medication. Treatment uses the antibiotic oxytetracycline, anti-inflammatories, and vitamins as well as turmeric powder as a topical treatment. With the handling and treatment given, the cow showed recovery within 2 weeks. There is a need to improve election management so that this miasis incident does not happen again. As well as the need for socialization from related departments regarding livestock diseases and livestock rearing management.